Transvection at the end of the truncated chromosome in Drosophila melanogaster. - Savitsky, M.; Kahn, T.; Pomerantseva, E.; Georgiev, P. (Genetics, 2003)
The phenomenon of transvection is well known for the Drosophila yellow locus. Thus enhancers of a promoterless yellow locus in one homologous chromosome can activate the yellow promoter in the other chromosome where the enhancers are inactive or deleted. In this report, we examined the requirements for trans-activation of the yellow promoter at the end of the deficient chromosome. A number of truncated chromosomes ending in different areas of the yellow regulatory region were examined in combination with the promoterless y alleles. We found that trans-activation of the yellow promoter at the end of a deficient chromosome required approximately 6 kb of an additional upstream sequence. The nature of upstream sequences affected the strength of transvection: addition of gypsy sequences induced stronger trans-activation than addition of HeT-A or yellow sequences. Only the promoter proximal region (within -158 bp of the yellow transcription start) was essential for trans-activation; i.e., transvection did not require extensive homology in the yellow upstream region. Finally, the yellow enhancers located on the two pairing chromosomes could cooperatively activate one yellow promoter.